Through Bridge Spin Coupling in Homo‐ and Heterobimetallic Porphyrin Dimers upon Stepwise Oxidations: A Spectroscopic and Theoretical Investigation. Issue 44 (30th June 2021) - Kumar, Amit; Usman, Mohammad; Samanta, Deepannita; Rath, Sankar Prasad
Abstract: We have described copper(II)‐iron(III) and copper(II)‐manganese(III) heterobimetallic porphyrin dimers and compared them with the corresponding homobimetallic analogs. UV‐visible spectra are very distinct in the heterometallic species while electrochemical studies demonstrate that these species, as compared to the homobimetallic analog, are much easier to oxidize. Combined Mössbauer, EPR, NMR, magnetic and UV‐visible spectroscopic studies show that upon 2e‐oxidation of the heterobimetallic complexes only ring‐centered oxidation occurs. The energy differences between HOMO and LUMO are linearly dependent with the low‐energy NIR band obtained for the 2e‐oxidized complexes. Also, strong electronic communication between two porphyrin rings through the bridge facilitates coupling between various unpaired spins present while the coupling model depends on the nature of metal ions used. While unpaired spins of Fe(III) and the porphyrin π‐cation radical are strongly antiferromagnetically coupled, such coupling is rather weak between Mn(III) and a porphyrin π‐cation radical. Moreover, the coupling between two π‐cation radicals are much stronger in the 2e‐oxidized complexes of dimanganese(III) and copper(II)‐manganese(III) porphyrin dimers as compared to their diiron(III) and copper(II)‐iron(III) analogs. Furthermore, coupling between the unpaired spins of a π‐cation radical and copper(II) is much stronger in the 2e‐oxidized complex of copper(II)‐iron(III) porphyrin dimer as compared to its copper(II)‐manganese(III) analog. The Mulliken spin density distributions in 2e‐oxidized homo‐ and heterobimetallic complexes show symmetric and asymmetric spread between the two macrocycles, respectively. In both the 2e‐oxidized heterobimetallic complexes, the Cu(II) porphyrin center acts as a charge donor while Fe(III)/Mn(III) porphyrin center act as a charge acceptor. The experimental observations are also strongly supported by DFT calculations. Abstract : Homo‐ and heterobimetallic porphyrin dimers have been synthesized, which, upon 2e‐oxidation, produce stable dication diradical species as shown. Through the bridge, both porphyrin rings exhibited notable conjugation resulting in effective coupling between metal and porphyrin radical spins of both rings while the coupling model dependent on the nature of metal ion used. Mulliken spin density distributions display the Cu(II) porphyrin center as charge donor while Fe(III)/Mn(III) porphyrin center as charge acceptor.